Prerehabilitation of patients qualified for prostatectomy based on own experience - Strojek, Katarzyna (Journal of Education, Health and Sport, 2025)
Introduction Prehabilitation involves comprehensive and multidirectional activities aimed at preparing the patient for surgery or other types of treatment (radiotherapy, chemotherapy). The main goal of the above-mentioned activities is to reduce the risk of complications, support the patient’s regeneration process and ensure a quick return to health and normal daily activities. Prehabilitation includes an interdisciplinary approach through activities in the preoperative period: improving physical condition, achieving a healthy body weight, proper nutrition, mental training, stopping addictions and changing bad habits. Numerous scientific reports indicate the beneficial effects of prehabilitation programs. Prehabilitation reduces the percentage of postoperative complications, shortens the length of hospital stay, increases physical activity, reduces treatment costs, reduces the number of antibiotics administered and has a positive effect on patients’ compliance with postoperative recommendations. Objectives The aim of the article was to present the author’s development of a prehabilitation program for patients qualified for radical prostatectomy due to prostate cancer. Preparing the patient for surgical treatment requires multidirectional and comprehensive action, which was developed in the Department of Physiotherapy, Faculty of Health Sciences, Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Toruń and implemented in the Urology Clinic of the University Hospital No. 2 dr. Jan Biziel in Bydgoszcz. The prehabilitation program was developed based on own experience in the course of direct work with oncological patients in the field of prostate cancer and through the analysis of the literature. Conclusions Prehabilitation is essential to ensure the highest quality of medical care for patients undergoing surgical treatment. Prehabilitation promotes the development of comprehensive care, placing the patient’s well-being at the center. The main goal of conducting a prehabilitation program by healthcare workers is to motivate the patient to lead a healthier lifestyle. Physical activity is a recommended preventive intervention to reduce postoperative complications. Prehabilitation is most effective in high-risk patients, and may be crucial for patients’ survival after surgical treatment. Employees employed in surgical, urological, gynecological, and oncological clinics should be aware of the importance of prehabilitation and create their own care programs for patients qualified for surgical treatment.